Predicting the stability and exploring the fundamental physical properties of tetragonal Gd2O3: A comprehensive first-principles investigation - Minhajul Islam; Md Abdur Rob Sheikh (Nuclear Materials and Energy)
A burnable absorber is a material used in nuclear reactors to manage reactivity and extend operational cycles by absorbing neutrons. Gadolinium oxide (Gd2O3) is a prevalent burnable absorber employed in nuclear reactors. By utilizing density functional theory (DFT) within a first-principles framework, a comprehensive exploration into the physical characteristics of the predicted tetragonal phase of Gd2O3 has been effectively conducted. The investigation encompasses structural, electronic, magnetic, elastic, mechanical, bonding, thermophysical, and optical aspects. Since tetragonal Gd2O3 has not been experimentally synthesized, the stability of the tetragonal phase is confirmed through assessments of its structural, lattice dynamical, thermodynamic, and mechanical attributes. Demonstrating semiconducting behavior, the electronic nature reveals a band gap of 1.241 eV. The density of states (DOS) illustration validates the semiconductor electronic character, and the calculated magnetic moment, determined through up-down spin DOS, is 3.06 μB/f.u. The Poisson’s ratio value reflects the dominance of ionic bonding in Gd2O3, a finding corroborated by bond population analysis. Impressively, the tetragonal Gd2O3 displays elevated lattice thermal conductivity value in comparison to its cubic, monoclinic, and hexagonal counterparts. Furthermore, the determined melting point registers at 1709.31 K. In the realm of optics, an analysis based on frequency dependence reveals that tetragonal Gd2O3 holds promise as a candidate for optoelectronic applications, particularly in the ultraviolet (UV) energy range.